Experience on Training among the Participants of Teaching Methodology and Assessment - Md Habib Ullah, Hadi; Jalal Uddin, Md; Kamrul Hasan, Md (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Recent development in medical education have created increasing challenges for medical teachers. Teachers are not born, they are made. Some special initiatives can make one able to be a good teacher. Teaching is not an inborn quality. A professional training is needed to be a teacher. In Bangladesh medical professionals become teachers without any sorts of formal training of teaching methodology and assessment. A Medical Degree is not the only qualification of a medical teacher. Our medical professional become teacher without any sort of formal training of “Teaching Methodology and Assessment”. To improve the quality of medical education in Bangladesh, training on teaching methodology and assessment for medical teachers is essential. This study was done to describe experience on training by trainers on teaching methodology and assessment. Materials and methods: This Experiental study (Before and after trial study) was conducted in the teachers of various Department of Chattagram Maa-O-Shishu Hospital Medical College, Chattogram (CMOSHMC) from July 2022 to December 2022. Sample size: 63 (24 Male, 39 Female) Results: 63 Participants were grouped into 3 groups ,21 participants were in each group. Each group participated in workshop for 4 days.They are trained with 12 modules supplied by CME. Pre-test and Post-test were conducted. Test results were analyzed for any significant difference. Among the First batch the mean score of pretest was 8.8+/- 1.7 and post-test was 11.6+/- 2.96, which was statistically significant. Second batch-the mean score of pre-test was 7.23 +/- 2.46 and post-test was11.55+/- 2.63, which was statistically significant. Third batch- the mean score of pre-test was 7.66+/- 2.17 and post-test was11.31+/- 2.62, which was also statistically significant. Conclusion: Training on teaching methodology and assessment is essential for medical professional development. So it should be continued periodically. Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 95-98